Ecopedagogy for Equitable Green Skills Development in School Education: A Systematic Literature Review - Fitri Sholihah; Yusuf Tri Herlambang; Yeni Yuniarti (Women, Education, and Social Welfare, 2026)
Environmental disruption requires school education to develop green skills that combine ecological literacy, systems thinking, collaboration, and action. This systematic literature review synthesizes how ecopedagogic approaches support equitable green-skills development and identifies reporting gaps relevant to inclusive education and social welfare. Following a PRISMA 2020-aligned protocol, the review examined an author-supplied corpus of 100 records retrieved from Scopus and Google Scholar for 2021–2026. After duplicate removal, title–abstract screening, and full-text eligibility assessment, 15 studies were included. Thematic synthesis identified five recurring pathways: critical and relational inquiry, interdisciplinary curriculum integration, place-based and outdoor learning, action-oriented projects, and critically mediated digital learning. Reported outcomes clustered around ecological literacy, critical and systems thinking, participation, collaboration, and environmental responsibility. However, gender-disaggregated outcomes and intersectional access conditions were seldom reported, preventing a defensible synthesis of differential benefits for girls, women, or other marginalized groups. The review proposes an Equity-Responsive Ecopedagogic Pathway framework linking pedagogy, green-skill outcomes, and reporting requirements.